2020
DOI: 10.1098/rspb.2019.2993
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of annual and seasonal immune investment in a temporal reproductive opportunist

Abstract: Historically, investigations of how organismal investments in immunity fluctuate in response to environmental and physiological changes have focused on seasonally breeding organisms that confine reproduction to seasons with relatively unchallenging environmental conditions and abundant resources. The red crossbill, Loxia curvirostra , is a songbird that can breed opportunistically if conifer seeds are abundant, on both short, cold, and long, warm days, providing an ideal system to inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…A small clutch size may allow red-capped larks to simultaneously maintain both reproduction and immune function. Long lived birds with a slower pace of life are associated with well-developed immune defences (Martin et al 2006 ; Lee et al 2008 ) and are known to favour investments that increase survival, including immune defenses, even under challenging conditions such as reproduction (Tella et al 2002 ; Ardia 2005 ; Lee 2006 ; Lee et al 2008 ; Tieleman et al 2019 ; Schultz et al 2020 ). On the other hand, birds in mid-to-high latitudes are short-lived and have a faster pace of life and supposedly invest in reproduction (large clutch size) at the expense of self-maintenance (Martin et al 2006 ; Lee et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A small clutch size may allow red-capped larks to simultaneously maintain both reproduction and immune function. Long lived birds with a slower pace of life are associated with well-developed immune defences (Martin et al 2006 ; Lee et al 2008 ) and are known to favour investments that increase survival, including immune defenses, even under challenging conditions such as reproduction (Tella et al 2002 ; Ardia 2005 ; Lee 2006 ; Lee et al 2008 ; Tieleman et al 2019 ; Schultz et al 2020 ). On the other hand, birds in mid-to-high latitudes are short-lived and have a faster pace of life and supposedly invest in reproduction (large clutch size) at the expense of self-maintenance (Martin et al 2006 ; Lee et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that different immune indices were differently influenced by environmental conditions using location as proxy for different climatic conditions. Temperature (Shephard et al 1998 ; Bowden et al 2007 ; Schultz et al 2020 ) and rainfall (Rubenstein et al 2008 ; Schultz et al 2020 ) have been shown to influence different components of immune function. Moreover, temperature (Watts et al 1987 ; Demas and Nelson 1998 ; Altizer et al 2006 ; Lowen et al 2007 ) and rainfall (Bicout and Sabatier 2004 ; Tieleman et al 2019 ) can influence both the broader geographical patterns and the short-term local dynamics of pathogens and diseases, which would be expected to drive immunological variation (Christe et al 2001 ; Møller et al 2003 ; Horrocks et al 2012b ; Tieleman et al 2019 ; Schultz et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations